Etnografi Ideasional (Suatu Metodologi Penelitian Kebudayaan) - Mudjahirin Thohir (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2019)
Ideational ethnography is the study of society and culture based on the assumption that every action is meaningful to the perpetrators. The hidden meaning behind the motives is knowledge that is assumed to be true. The source of truth is belief (constitutive truth); reasoning and experience (cognitive truth), or evaluative reality as in tradition. In ideational ethnographic research, the task of researchers is to seize the meaning referred to as the truth behind the cultural actions of the people studied. While the technique of digging data used is observation, interviews, and documents according to the context of the problem (reality) being studied.In ideational ethnographic research, reality is seen in five levels, namely reality: empirical, symbolic, meaning, ideas, and values (worldview). How are the five realities seen from their perspective (emic perspective) as an example of sea ritual (labuh).